Collaboration Families in School Education (Journal of Parents and Teachers, 2014)
It is important that families participate in school education, as building a genuine educational community and engaging parents with the education of their children is essential in the teaching and learning process. However, it is necessary to learn how to develop this collaboration.
Keywords: collaboration; school; family; education; scholar; scholar counsellor; social; children.